Unionized Oligopoly and Outsourcing - Melkumian, Arsen V. (2009)
The interaction between labor unions and international competition has received a lot of attention. In the first decade of the 21st century, increasing number of companies in unionized oligopolistic industries has shifted production abroad. However, the issue of outsourcing in the context of a unionized duopoly has received little attention. In this paper, I model the option to outsource in the context of unionized labor markets in exporting industries. I show that if the inverse demand function is convex, then an increase in the foreign wage increases the utility of a wage neutral union. I find that if the domestic firm can credibly threaten to shift production abroad, then an increase in the outsourcing country’s wage may increase domestic profits if the union is labor-oriented.